Structural health monitoring of green concrete - Zhang, Shiming (2012)
Green concrete becomes more popular around the world these years, however, amount of recycled materials used in green concrete have some uncertainties which might affect the performance of concrete. Thus, compressive tests for recycled aggregates concrete cylinders are carried out, to find out the applicable percentage of recycled aggregates replacement by natural aggregate in green concrete mix design; moreover, two reinforced concrete beams contained 0% and the applicable percentage of recycled aggregate were designed and cast to check the consistency of the conclusions made from concrete cylinders.